Hubungan citra tubuh dengan kesejahteraan spiritual pada pasien hemodialisis di RS PKU Muhammadiyah Gamping - Tendy Ar Riqi; Sutejo Sutejo; Erika Nurwidayanti (Poltekkes Kemenkes Yogyakarta, 2019)
Hemodialysis would affect body image and have an impact on the spiritual wellbeing of patients due to the variety of changes in the patient’s body. The purpose of this study was to determine the relationship between body image and the spiritual wellbeing of patients undergoing hemodialysis. The research method is descriptive correlative with a cross-sectional approach. The study was conducted in PKU Muhammadiyah Hospital Gamping with a sample of 60 respondents. The sampling method is purposive sampling. Data collection tool in this study is a questionnaire with 22 statements. Data were analyzed using univariate and bivariate analysis using chi square tests. The results showed that there is a relationship between body image and the spiritual wellbeing of patients with chronic renal failure undergoing hemodialysis with p-value (0,027) < ? (0,05). This study recommends hemodialysis unit to improve further performance in providing comprehensive care nursing practice both physical and psychosocial in patients with chronic renal failure undergoing hemodialysis especially on the subject of body image disturbance that will affect the spiritual wellbeing of patients.